Effects of ischemic conditioning on maximal voluntary plantar flexion contractions - Oliveira Cruz, Rogerio Santos de [UNESP]; Pereira, Kayo Leonardo; Aguiar, Rafael Alves de; Turnes, Tiago; Denadai, Benedito Sergio [UNESP]; Caputo, Fabrizio (Elsevier B.V., 2019)
Intermittent blood flow restriction to local or remote vascular beds induces endogenous protection against ischemia-reperfusion injury in several tissues and organs. When applied non-invasively by placing occlusion cuffs on the limbs, this ischemic conditioning has been shown to elicit an acute ergogenic response. However, the underlying mechanisms behind this phenomenon remain unknown. Prior research suggest that ischemic conditioning may operate via improved motor discharges from the central nervous system, thus enhancing the electrochemical activation and force generation of agonist muscles. Here we show that, for healthy individuals performing maximal voluntary contractions of the plantar flexors, the acute benefit elicited by ischemic conditioning on maximal isometric ankle torque production is largely explained by parallel gains in the surface myoelectrical activity of the triceps surae. However, the magnitude of this response appears to vary between individuals. These findings indicate that enhanced levels of agonist activity contribute to the ergogenic effect of ischemic conditioning during maximal efforts, thereby enabling more direct assessments of neural output following the procedure.
Keywords: Vascular occlusion; Dynamometric performance; Force generation; Interference sEMG signals; Skeletal muscle